Quantitative Analysis of Chemotherapeutic Effects in Tumors Using In Vivo Staining and Correlative Histology - Heung Kook Choi; Doreen Yessayan; Hyun Ju Choi; Eyk Schellenberger; Alex Bogdanov; Lee Josephson; Ralph Weissleder; Vasilis Ntziachristos (Cellular Oncology, 2005)
Aims: To microscopically analyze the chemotherapeutic response of tumors using in vivo staining based on an annexinV-Cy5.5 probe and independently asses their apoptotic count using quantitative histological analysis. Methods: Lewis Lung Carcinomas cells, that are sensitive (CS-LLC) and resistant (CR-LLC) to chemotherapy were implanted in nude mice and grown to tumours. Mice were treated with cyclophosphamide and injected with a Cy5.5-annexinV fluorescent probe. In vivo imaging was performed using Fluorescence Molecular Tomography. Subsequently tumours were excised and prepared for histology. The histological tumour sections were stained for apoptosis using a terminal deoxynucleotidyl transferase-mediated nick end labeling (TUNEL) assay. A minimum of ten tissue sections were analyzed per tumour for apoptosis quantification by TUNEL staining and corresponding Cy5.5 distribution. Results: We detected higher levels of apoptosis and corresponding higher levels of Cy5.5 fluorescence in the CS-LLC vs. the CR-LLC tumours. The cell count rate on CS-LLC sections over CR-LLC was found to be ∼2 :1 where the corresponding area observed on Cy5.5 distribution measurements revealed a ∼1.7 :1 ratio of CS-LLC over CR-LLC. These observations are consistent with the higher apoptotic index expected from the CS-LLC cell line. Conclusions: Quantitative analysis of histological slices revealed higher fluorescence and higher apoptotic count in the CS-LLC tumour images compared to the CR-LLC tumour images. These observations demonstrate that the annexinV-Cy5.5 probe sensed the chemotherapeutic effect of cyclophospamide and further confirmed in vivo FMT measurements.